Simulation of a Centrifugal Pump by Using the Harmonic Balance Method - Franco Magagnato; Jinfeng Zhang (International Journal of Rotating Machinery)
The harmonic balance method was used for the flow simulation in a centrifugal pump. Independence studies have been done to choose proper number of harmonic modes and inlet eddy viscosity ratio value. The results from harmonic balance method show good agreements with PIV experiments and unsteady calculation results (which is based on the dual time stepping method) for the predicted head and the phase-averaged velocity. A detailed analysis of the flow fields at different flow rates shows that the flow rate has an evident influence on the flow fields. At 0.6Qd, some vortices begin to appear in the impeller, and at 0.4Qd some vortices have blocked the flow passage. The flow fields at different positions at 0.6Qd and 0.4Qd show how the complicated flow phenomena are forming, developing, and even disappearing. The harmonic balance method can be used for the flow simulation in pumps, showing the same accuracy as unsteady methods, but is considerably faster.